Mesiodistal and Buccolingual Dimensions in Croatian Orthodontic Hypodontia Patients' Teeth - Antun Vidaković; Sandra Anić-Milošević; Daša Nikolov Borić; Senka Meštrović (University of Zagreb. School of Dental Medicine, 2018)
Objective: This study compared mesiodistal (MD) and buccolingual (BL) tooth dimensions of hypodontia patients with a control group with complete dentition. The null hypothesis was that there was no difference in tooth sizes between hypodontia patients and the controls. Methods: The sample comprised 76 patients with hypodontia (50 female and 26 male) aged between 11 and 18 years. The control group comprised 50 females and 26 males with the same age range as the study group. Mesiodistal (MD) and buccolingual (BL) dimensions were measured on pretreatment dental casts with a digital caliper to the nearest 0.01 mm. The data were analyzed using Statistica 7.1 (StatSoft Inc.) statistical package (descriptive statistics, test of distribution normality, parametric statistics). Results: The most common congenitally missing teeth were the lower second premolars (left 13.45% and right 13.90%) and upper lateral incisors (both left and right 12.56%), followed by upper second premolars (right 9.4o% and left 10.31%). The greatest differences between the study and control group were found in upper lateral incisors, 8.08% in MD and 6.40% in BL dimension. The smallest difference was found in BL dimension of lower lateral incisor (2.37%), MD dimension of lower second premolars and upper first molar (2.61%) and MD dimension of lower central incisor (2.26%). Conclusion: The teeth are smaller in subjects with hypodontia than those of the controls on average 4.02% in MD dimension and 3.85% in BL dimension. The tooth that showed the greatest difference in tooth dimension was maxillary lateral incisor.